Technological salvation - Štivić, Stjepan (Poligrafi, 2025)
This paper critically examines Neuralink’s public campaign and promotional strategies through the lens of religious symbolism and marketing ideas. positioned as a leader in brain-computer interface (BCi) development, Neuralink frames its technology not only as a groundbreaking medical intervention, capable of restor-ing various neurological problems, but also as a pathway toward human enhance-ment. The central argument is that Neuralink’s marketing model appropriates elements of Christian religious symbolism, particularly embedding the messianic attributes of Jesus Christ. Through analysis of its messaging, media presence, and charismatic leadership, the paper contends that Neuralink constructs a narrative of technological salvation. This symbolic framing serves not only to generate pub-lic trust and enthusiasm but also to distinguish Neuralink within the competitive landscape of emerging neuroethologies.
Keywords: brain-computer interfaces (BCI); marketing model; marketinški model; Neuralink; religious symbolism; technological salvation; tehnološka odrešitev; verska simbolika